Airman's Information Manual 1981 / Basic Flight Information and ATC Procedure - Winner Walter P (Aviation Maintenance Publishers, 1981)
Basic Information and ATC Procedures (Reprint of the Latest Complete FAA Issue), Pilot/ Controller Glossary, Index, Airport/ Facility Directory (Excerpts), Notices to Airmen (Excerpts), Graphic Notices and Supplemental Data (Excerpts).